2018
DOI: 10.1155/2018/6869705
|View full text |Cite
|
Sign up to set email alerts
|

Association of Androgen Excess with Glucose Intolerance in Women with Polycystic Ovary Syndrome

Abstract: Women with polycystic ovary syndrome (PCOS) show high prevalence of glucose intolerance. This study aimed to investigate the association of androgen excess with glucose intolerance in PCOS. A total of 378 women with PCOS participated in the study. Free androgen index (FAI) was selected as indicator of hyperandrogenism. Insulin sensitivity was assessed by 1/homeostasis model assessment of insulin resistance (1/HOMA-IR) and Matsuda insulin sensitivity index (ISIM); β-cell function was assessed by disposition ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
4
27
1
Order By: Relevance
“…Furthermore, insulin directly stimulates androgen synthesis by the theca cell. Therefore, the improvement of insulin sensitivity and the resultant decrease in circulating insulin could decrease testosterone levels, as previously reported, that improvement in insulin resistance through weight loss or the use of insulin-sensitizing drugs leads to a decrease in hyperandrogenemia [43,44]. For the rst time, we observed that thylakoid-rich spinach extract with a hypocaloric diet decreased DBP and serum levels of hs-CRP, without effect on the SBP in obese women with PCOS after 12 weeks.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, insulin directly stimulates androgen synthesis by the theca cell. Therefore, the improvement of insulin sensitivity and the resultant decrease in circulating insulin could decrease testosterone levels, as previously reported, that improvement in insulin resistance through weight loss or the use of insulin-sensitizing drugs leads to a decrease in hyperandrogenemia [43,44]. For the rst time, we observed that thylakoid-rich spinach extract with a hypocaloric diet decreased DBP and serum levels of hs-CRP, without effect on the SBP in obese women with PCOS after 12 weeks.…”
Section: Discussionsupporting
confidence: 71%
“…Rather, they are closely associated with testosterone levels (Holte et al 1994). Finally, there is a robust relationship between β cell dysfunction and testosterone concentrations in these women (Goodarzi et al 2005, Zhang et al 2018. Since the AR is expressed in β cells in females, this raises the possibility that excess testosterone produces insulin hypersecretion and β cell dysfunction.…”
Section: Testosterone Action In β Cells In Womenmentioning
confidence: 99%
“…Several factors support the fact that hyperandrogenism can determine the characteristic phenotype PCOS, including, abnormalities of the menstrual cycle, hirsutism and polycystic ovaries [35][36][37]. Excessive levels of androgens may also promote insulin resistance and the dysfunction of β-cells in PCOS patients [38]. One previous study showed implicated lncRNA H19 in the development of neuroendocrine prostate cancer (NEPC), an androgen-related disease; this was suggestive of a potential regulatory role for lncRNA H19 expression with androgen levels [28].…”
Section: Discussionmentioning
confidence: 98%